Investigation of rice Husk/CNTs composites performance in microwave properties - Yew, B.S (2014)
This paper is to study the performance of rice husk and carbon-nanotubes nanotubes (RH-CNTs) composite material as a microwave absorber. The rice husk (RH) is a lossy material that contains dielectric properties which suitable used as microwave absorber. The dielectric properties are playing a main role in microwave absorption of any material. The dielectric properties of materials were measured using an Agilent dielectric probe. The microwave absorption performance of rice husk and CNTs composites was investigated by using rectangular waveguide transmission line in simulation. The microwave absorbers were designed and simulated using the Computer Simulation Technology Microwave studio software (CST-MWS). The ability of microwave absorption between rice husk and RH-CNTs was compared in 8.2-12.4 GHz. The microwave absorption with different thickness of RH-CNTs samples was investigated. The results show that the RH-CNTs composites have a better ability of microwave absorption compared than pure rice husk.